Colloid chemistry in mineral processing - Laskowski, J. (Janusz), 1936-; Ralston, J. (Developments in mineral processing, 1992)
Within this volume is a thorough coverage of the fundamental principles embracing modern theories of colloid chemistry applied to mineral processing. It is written in respect for Dr. J.A. Kitchener, distinguished Reader in the Science of Mineral Processing in the Royal School of Mines, Imperial College, University of London (recently retired). Dr. Kitchener's expertise in colloid chemistry has led to numerous fundamental insights and practical advances in flotation, selective flocculation, and the treatment of slimes. Colloid chemistry is inevitably involved in all aspects of mineral processi.